(untitled) (Research, Society and Development, 2022)
The freestanding birth centers (FBC) are health institutions that offer ante, intra and postnatal care to healthy women and babies, standing out for their philosophy of care and practice based on the humanized and biopsychosocial model of care. Despite having excellent health indicators, these institutions don´t have support for maintenance and expansion in Brazil. This article aims to describe a scoping review protocol that will map the characteristics of the model of care in Brazilian FBC. This review protocol was registered on the Open Science Framework (OSF) platform and developed according to the recommendations of the JBI Manual for Evidence Synthesis and PRISMA-ScR. The review steps are: the definition of descriptors and eligibility criteria, the search for studies in databases and repositories, the studies selection and data extraction and, finally, how the results will be presented. With this review, it is expect to map the existing scientific knowledge about how FBC are structured and organized in Brazil, how they are accessed by the population, what are the care outcomes for women and babies and how service users and healthcare professionals experience the FBC model of care. Moreover, this study has the potential to enhance the urgent debate to build strategies to improve maternal and infant health indicators in the country.